Separator for electrochemical device, electrode assembly including same, and electrochemical device

By optimizing the ratio of inorganic fillers and polymer combinations in the lithium-ion battery separation membrane, the problem of insufficient thermal stability of the separation membrane at high temperature is solved, the adhesion between electrodes is improved, and the safety and performance of the lithium-ion battery is ensured.

JP7650976B2Active Publication Date: 2025-03-25LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023532410
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-27
Filing Date
2022-08-26
Publication Date
2025-03-25
Estimated Expiration
2042-08-26

AI Technical Summary

Technical Problem

The separation membrane of existing lithium-ion batteries does not have sufficient thermal stability at high temperatures, which can easily lead to short circuits. At the same time, in the process of increasing thermal stability, the conductivity of the separation membrane increases and the adhesion between the electrodes decreases, affecting the safety and performance of the battery.

Method used

By optimizing the ratio of inorganic filler and polymer combination in the multi-layer structure of the separation membrane, 20≦[inorganic filler content (wt%) × inorganic filler BET surface area (m²/g)]/[polymer content (wt%)]≦30 is ensured, and the distribution of polymer and surface polymers covered by the inorganic filler surface is adjusted to improve the thermal stability of the separation membrane and the adhesion between electrodes.

Benefits of technology

The thermal stability of the separation membrane at high temperature and the stable adhesion between electrodes are achieved, ensuring the safety and performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007650976000003
    Figure 0007650976000003
  • Figure 0007650976000001
    Figure 0007650976000001
  • Figure 0007650976000002
    Figure 0007650976000002
Patent Text Reader

Abstract

The present invention provides a separator for an electrochemical device, The separation membrane comprises a porous substrate and a porous coating layer formed on at least one surface of the porous substrate; the porous coating layer includes a binder polymer and an inorganic filler; The present invention provides a separator for electrochemical devices, which satisfies the following formula 1: [Formula 1] 20≦[content of inorganic filler (wt%) × BET surface area of ​​inorganic filler (m 2 / g)] / [binder polymer content (wt%)]≦30 (The content of the binder polymer and the content of the inorganic filler are based on 100% by weight of the total amount of the porous coating layer.) The separator for an electrochemical device according to the present invention not only ensures the safety of the electrochemical device, but also improves the adhesive strength between the porous substrate of the separator and the porous coating layer, and the adhesive strength between the separator and the electrodes, thereby improving heat resistance stability.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator for an electrochemical device, an electrode assembly including the same, and an electrochemical device.

[0002] This application claims priority to Korean Patent Application No. 10-2021-0114280, filed on August 27, 2021, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] In recent years, interest in energy storage technology has been increasing. As the fields of application expand to include energy for mobile phones, video cameras, and laptops, as well as electric vehicles, efforts in the research and development of electrochemical elements have become more and more concrete. Electrochemical elements are the field that has attracted the most attention in this regard, and among them, secondary batteries that can be charged and discharged, secondary batteries that are thin and applicable to various products, and lithium secondary batteries with high energy density are the focus of attention. Recently, great attention has been paid to ensuring safety in the development of such secondary batteries.

[0004] In currently produced lithium secondary batteries, a porous substrate using a polyolefin polymer resin is used as a separator substrate to prevent short circuit between the positive and negative electrodes. However, the porous substrate has a problem of low heat resistance, such as shrinking or melting at high temperatures, which can cause short circuit. To solve the above problem, a method of improving heat resistance by forming a porous coating layer containing a mixture of an inorganic filler and a binder polymer on at least one surface of the porous substrate is widely used. However, the introduction of the porous coating layer causes other problems, such as an increase in the resistance of the separator and a decrease in adhesion between electrodes, and solutions to these problems are required.

[0005] In addition, in order to increase the energy density of the battery and reduce the resistance of the separator, there have been attempts to manufacture a thinner separator to reduce the thickness of the battery. However, if the separator is thin, the adhesive strength between the separator and the electrode is reduced, which reduces the ease of assembly and the safety of the battery. For this reason, there is a demand for a separator that can achieve stable adhesive strength in the battery and ensure heat resistance even if it is thin.

[0006] Among the methods for manufacturing a separator by introducing a porous coating layer, when a wet phase separation method is applied, a slurry containing a mixture of an inorganic filler and a binder polymer is coated on a porous substrate, and then the separator is manufactured by wet phase separation. In this case, the more the binder polymer is distributed on the surface of the porous coating layer, the more the adhesion to the electrode can be improved. To achieve this, it is necessary to develop an optimal ratio of the inorganic filler and the binder polymer in the porous coating layer. Summary of the Invention [Problem to be solved by the invention]

[0007] Therefore, an object of the present invention is to provide a separator for an electrochemical device, which ensures the safety of the electrochemical device, improves the adhesive strength between the porous substrate of the separator and the porous coating layer, and between the separator and an electrode, and improves heat resistance stability, and an electrochemical device including the same.

[0008] It will be readily apparent that other objects and advantages of the present invention can be realized by the means or methods recited in the claims, and combinations thereof. [Means for solving the problem]

[0009] The present inventors have found that the above problems can be solved by the following separator for an electrochemical device and an electrochemical device including the separator.

[0010] The first embodiment is A separator for an electrochemical device, comprising: The separation membrane comprises a porous substrate and a porous coating layer formed on at least one surface of the porous substrate, The porous coating layer includes a binder polymer and an inorganic filler, The present invention relates to a separator for electrochemical elements, which satisfies the following formula 1: [Formula 1] 20≦[Inorganic filler content (wt%) × BET surface area of ​​inorganic filler (m 2 / g)] / [Binder polymer content (wt%) ≦30 (The content of the binder polymer and the content of the inorganic filler are based on 100% by weight of the total amount of the porous coating layer.)

[0011] The second embodiment is the same as the first embodiment, The present invention relates to a separator for electrochemical elements, which satisfies the following formula 2: [Formula 2] 23≦[Inorganic filler content (wt%) × BET surface area of ​​inorganic filler (m 2 / g)] / [Binder polymer content (wt%) ≦28 (The content of the binder polymer and the content of the inorganic filler are based on 100% by weight of the total amount of the porous coating layer.)

[0012] The third embodiment is the first or second embodiment, The inorganic filler has a BET surface area of ​​10 to 20 m 2 The present invention relates to a separator for electrochemical elements, comprising an inorganic filler having a molecular weight of 1 / g.

[0013] The fourth embodiment is any one of the first to third embodiments, The content of the inorganic filler is 50 to 80% by weight based on 100% by weight of the total amount of the porous coating layer; The content of the binder polymer is 20 to 50% by weight relative to 100% by weight of the total amount of the porous coating layer.

[0014] The fifth embodiment is any one of the first to fourth embodiments, The binder polymer is Polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethylmethacrylate, polybutylacrylate, polybutylmethacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate The present invention relates to a separator for an electrochemical element, which is made of a material selected from the group consisting of cyanoethyl propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxyl methyl cellulose, and a mixture of two or more of these.

[0015] The sixth embodiment is any one of the first to fifth embodiments, The present invention relates to a separator for an electrochemical element, characterized in that the adhesive strength (peel strength) between the porous substrate and the porous coating layer of the separator is 200 gf / 15 mm or more.

[0016] The seventh embodiment relates to an electrode assembly including two electrodes having opposite polarities and a separator interposed between the two electrodes, wherein the separator includes any one of the separators of the first to sixth embodiments.

[0017] The eighth embodiment is the seventh embodiment, The present invention relates to an electrode assembly, wherein the adhesive strength (lamination strength) between the electrode and the separator is 100 gf / 25 mm or more.

[0018] The ninth embodiment relates to an electrochemical device comprising one or more electrode assemblies according to the seventh or eighth embodiment.

[0019] The tenth embodiment is the ninth embodiment, The electrochemical device is a lithium secondary battery. Effect of the Invention

[0020] The separator for an electrochemical device according to the present invention includes a binder polymer in a predetermined content range determined in consideration of the BET (Brunauer, Emmett, Teller) surface area of ​​the inorganic filler and the content of the inorganic filler, whereby the binder polymer covering the surface of the inorganic filler and the binder polymer located on the surface of the porous coating layer can be appropriately distributed in the porous coating layer.

[0021] Therefore, the adhesive strength between the porous substrate of the separator and the porous coating layer, and between the separator and the electrodes, are improved, and the heat resistance stability is improved. [Brief description of the drawings]

[0022] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to facilitate a better understanding of the technical concept of the present invention together with the above-described contents of the invention, and therefore the present invention should not be interpreted as being limited only to the matters depicted in such drawings. Meanwhile, the shape, size, scale, ratio, etc. of elements in the drawings described in this specification may be exaggerated in order to emphasize a clearer description.

[0023] [Figure 1] 1 shows SEM images of a cross section of the separation membrane of Example 1. Specifically, the images show enlarged cross sections of the surface of the porous coating layer of the separation membrane of Example 1, a cross section of the separation membrane, and an enlarged cross section of the porous substrate (polyethylene polymer film). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The present invention will be described in detail below. The terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as meanings and concepts that are appropriate to the technical idea of ​​the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.

[0025] Throughout this specification, when a part is described as "comprising" or "having" certain elements, this does not mean that other elements are excluded, but that other elements may also be included, unless otherwise specified.

[0026] In addition, the terms "approximately" and "about" used throughout this specification are used to mean a numerical value or a value close to the numerical value when the tolerances of manufacturing and materials inherent in the referred meaning are given, and are used to prevent unscrupulous infringers from unfairly taking advantage of the disclosure in which exact numerical values ​​or absolute numerical values ​​are mentioned to aid in the understanding of the present invention.

[0027] Throughout this specification, the term "A and / or B" means "A or B, or both."

[0028] The present invention relates to a separator for an electrochemical device, an electrode assembly including the same, and an electrochemical device.

[0029] In general, when a porous coating layer having a small thickness is included in order to achieve a thin electrochemical device, there is a problem that the adhesive strength (peel strength) between the porous coating layer and the porous substrate and the adhesive strength (lamination strength) between the electrode and the separator are significantly reduced. In addition, there is a problem that the heat resistance of the porous substrate is low, which is not advantageous in ensuring the safety of the electrochemical device.

[0030] Therefore, the present inventors have focused on these problems and aim to provide a separator for electrochemical elements which exhibits sufficient adhesive strength (peel strength and lamination strength) and excellent heat resistance stability, and ensures safety.

[0031] The separator for an electrochemical device of the present invention will be described in detail below.

[0032] The separator for an electrochemical device according to the present invention comprises a porous substrate and a porous coating layer formed on at least one surface of the porous substrate, the porous coating layer including an inorganic filler and a binder polymer and satisfying the following [Formula 1]:

[0033] [Formula 1] 20≦[Inorganic filler content (wt%) × BET surface area of ​​inorganic filler (m 2 / g)] / [Binder polymer content (wt%) ≦30 (The content of the binder polymer and the content of the inorganic filler are based on 100% by weight of the total amount of the porous coating layer.)

[0034] Specifically, the porous coating layer of the separator of the present invention contains a binder polymer in a predetermined content range determined in consideration of the BET surface area of ​​the inorganic filler and the content of the inorganic filler, and as a result, the binder polymer covering the surface of the inorganic filler and the binder polymer located on the surface of the porous coating layer are appropriately distributed in the porous coating layer, thereby providing a well-balanced and excellent effect in terms of adhesive strength (peel strength and lamination strength) and heat resistance stability.

[0035] In particular, the separator of the present invention can exhibit excellent effects in terms of adhesive strength between the electrode and the separator, adhesive strength between the porous substrate and the porous coating layer, and heat resistance stability, compared to separators having the same or equivalent content ratio of inorganic filler and binder polymer in the porous coating layer as the present invention.

[0036] Meanwhile, in the case of a separator manufactured by a wet phase separation method, a binder polymer and an inorganic filler are mixed in the porous coating layer, and a binder is used to ensure the binding strength between the inorganic fillers. Therefore, it is important to appropriately adjust the amount of binder polymer required for binding the inorganic filler and the binder polymer, and the amount of binder polymer located on the surface of the porous coating layer to ensure the adhesive strength with the electrode. According to the present invention, since the amount of binder polymer in the porous coating layer of the separator manufactured by the wet phase separation method can be appropriately adjusted, there is an advantage that the separator manufactured by the wet phase separation method can also exhibit the desired effect.

[0037] In the present invention, the electrochemical device is a device that converts chemical energy into electrical energy by an electrochemical reaction, and includes all devices that perform electrochemical reactions, and specific examples include all types of primary batteries, secondary batteries, fuel cells, solar cells, and capacitors such as supercapacitor devices, etc. In particular, among the secondary batteries, lithium secondary batteries including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, and lithium ion polymer secondary batteries are preferred.

[0038] In the present invention, the separation membrane comprises a porous substrate and a porous coating layer formed on at least one surface of the porous substrate.

[0039] The porous substrate may refer to a substrate having a plurality of pores formed therein, which functions as a porous ion-conducting barrier that allows ions to pass while blocking electrical contact between the negative electrode and the positive electrode. The pores are interconnected so that gas or liquid can pass from one side of the substrate to the other side. As such a porous substrate, a porous polymer film containing a thermoplastic resin can be used in terms of providing a shutdown function. Here, the shutdown function refers to a function in which, when the battery temperature becomes high, the thermoplastic resin dissolves and blocks the pores of the porous substrate, blocking the movement of ions and preventing thermal runaway of the battery. Non-limiting examples of the thermoplastic resin include polyolefin resins such as polyethylene, polypropylene, polybutylene, and polypentene. Meanwhile, in terms of the shutdown function, the melting point of the thermoplastic resin is preferably less than about 200°C.

[0040] The thickness of the porous substrate is not particularly limited, but is specifically about 1 to 100 μm, more specifically about 5 to 50 μm, or about 5 to 30 μm. The porosity of the porous substrate is also not particularly limited, but is preferably about 10 to 95%, or about 35 to 65%.

[0041] The porous coating layer is formed on at least one surface of the porous substrate and includes an inorganic filler and a binder polymer.

[0042] In the present invention, the porous coating layer is filled with the inorganic fillers and bound to each other by the binder polymer in a state where the inorganic fillers are in contact with each other, so that interstitial volumes may be formed between the inorganic fillers. The interstitial volumes between the inorganic fillers may have a structure in which pores are formed as empty spaces.

[0043] In the present invention, the porous coating layer may be formed on one or both sides of the porous substrate. The total thickness of the porous coating layer is not particularly limited, but may be specifically about 1 to 50 μm, more specifically about 1 to 20 μm, about 1 to 10 μm, or about 1 to 5 μm. In particular, the separator of the present invention has an advantage that even if it includes a thin porous coating layer, the problem of reduced adhesive strength between the electrode and the separator does not occur.

[0044] In the present invention, the BET surface area of ​​the inorganic filler, the content of the inorganic filler, and the content of the binder polymer satisfy a value of 20 to 30 calculated from the following [Formula 1].

[0045] In a specific embodiment of the present invention, the value calculated from the following [Formula 1] can satisfy 23 to 28 or 23 to 27.

[0046] [Formula 1] [Inorganic filler content (wt%) × BET surface area of ​​inorganic filler (m 2 / g)] / [Content of binder polymer (wt%)] (The content of binder polymer and the content of inorganic filler are based on 100 wt% of the total amount of the porous coating layer.)

[0047] Specifically, the porous coating layer includes a binder polymer in a predetermined content range determined in consideration of the BET surface area of ​​the inorganic filler and the content of the inorganic filler.

[0048] Thus, the amount of binder polymer covering the surface of the inorganic filler can be optimized to sufficiently bind the inorganic filler and the binder polymer, and the amount of binder polymer located on the surface of the porous coating layer can be optimized to sufficiently ensure adhesion between the electrode and the separator.

[0049] Therefore, not only the adhesive strength between the porous substrate of the separator and the porous coating layer is improved, but also the adhesive strength between the separator and the electrode is improved.

[0050] In the present invention, the inorganic filler may be an inorganic filler having a BET surface area that satisfies the value of the above [Formula 1]. For example, the inorganic filler may have a BET surface area of ​​10 to 20 m 2 / g or 13~18m 2 From the viewpoint of producing a porous coating layer slurry, by including an inorganic filler having a BET surface area in the above range, the BET surface area value of 6 m, which has been generally used for a porous coating layer, can be reduced. 2 / g, it is possible to use less dispersant and minimize the dispersion process. If the BET surface area of ​​the inorganic filler is too large, the surface area covered by the binder polymer increases, and the binder polymer used to ensure the adhesive strength (lamination strength) between the electrode and the separator may relatively decrease. On the other hand, if the BET surface area of ​​the inorganic filler is too small, the amount of binder polymer distributed near the surface of the porous coating layer decreases, which may make it difficult to ensure the adhesive strength (peel strength) between the porous substrate and the porous coating layer, and therefore, it may also be difficult to ensure the adhesive strength (lamination strength) between the electrode and the separator.

[0051] However, the BET specific surface area of the inorganic filler is not necessarily limited to those satisfying the above range, and an inorganic filler having an appropriate BET specific surface area within the range that can achieve the object of the present invention while satisfying the value of the above [Formula 1] can be used.

[0052] The specific type of the inorganic filler is not particularly limited as long as it is electrochemically stable and no oxidation and / or reduction reaction occurs in the operating voltage range of the applied electrochemical element (for example, 0 to 5 V based on Li / Li+). For example, as the inorganic filler, there are AlOOH, Al(OH)3, ZrO2, BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3 (PLZT), Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC or a mixture thereof, etc. In addition to these, lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y series glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), SiS2 series glass (Li x Si yS z ., 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5 series glass (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7) or may further contain two or more of these inorganic fillers.

[0053] For example, in the present invention, when the porous coating layer contains a first inorganic filler and a second inorganic filler as at least two inorganic fillers, the separation membrane for an electrochemical element according to the present invention may satisfy the following [Formula 2].

[0054] [Formula 2] [(content (wt%) of the first inorganic filler × BET surface area (m 2 / g) of the first inorganic filler) + (content (wt%) of the second inorganic filler × BET surface area (m 2 / g) of the second inorganic filler)] / [content (wt%) of the binder polymer]

[0055] In the present invention, the binder polymer is not particularly limited as long as it can provide a binding force between inorganic fillers and between the porous coating layer and the electrode. For example, the binder polymer may be polyvinylidene fluoride-co-hexafluoropropylene (PVDF-co-HFP), polyvinylidene fluoride-co-trichloro ethylene, polyvinylidene fluoride-co-chlorotrifluoro ... ethylene), poly(methyl)methacrylate, polyethyl(meth)acrylate, poly n-propyl(meth)acrylate, polyisopropyl(meth)acrylate, poly n-butyl(meth)acrylate, poly t-butyl(meth)acrylate, poly sec-butyl(meth)acrylate, polypentyl(meth)acrylate, poly 2-ethylbutylpoly(meth)acrylate, poly 2-ethylhexyl(meth)acrylate, poly n-octyl(meth)acrylate, polyisooctyl(meth)acrylate, polyisononyl(meth)acrylate, polylauryl(meth)acrylate, polytetradecyl(meth)acrylate, poly N-vinylpyrrolidinone, polyacrylonitrile, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, cellulose acetate acetate), cellulose acetate butyrate, cellulose acetate propionateThe polyvinyl alcohol may be one or a mixture of two or more selected from the group consisting of acrylonitrile-styrene-butadiene copolymer, acrylonitrile-styrene-butadiene copolymer, and polyimide.

[0056] Specifically, in the present invention, the binder polymer may include a non-dispersant binder polymer and a dispersant binder polymer.

[0057] The dispersant binder polymer is a polymer having at least one dispersion-contributing functional group in the main chain or side chain of the polymer, and the dispersion-contributing functional group may be an OH group, a CN group, etc. Examples of such dispersant binder polymers include cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxyl methyl cellulose. Examples of non-dispersant binder polymers include the above binder polymers excluding the dispersant binder polymer.

[0058] In an embodiment of the present invention, the binder polymer may be a combination of a dispersant binder polymer and a non-dispersant binder polymer. When the binder polymer is a combination of a dispersant binder polymer and a non-dispersant binder polymer, the weight ratio of the dispersant binder polymer to the non-dispersant binder polymer may be 1:5 to 1:20, or 1:10 to 1:15. When such a weight ratio is satisfied, the dispersibility in the porous coating layer can be stabilized and the electrode adhesion after coating can be secured.

[0059] In the present invention, the content of the inorganic filler in the porous coating layer may be 50 to 80 wt%, 60 to 80 wt%, or 60 to 70 wt%, based on 100 wt% of the total amount of the porous coating layer. In addition, the content of the binder polymer in the porous coating layer may be 20 to 50 wt%, 30 to 50 wt%, or 35 to 50 wt%, based on 100 wt% of the total amount of the porous coating layer. By including the inorganic filler and the binder polymer in the weight ratio within the above range, the heat resistance of the separator can be improved, and the adhesive strength between the porous substrate and the porous coating layer, and the adhesive strength between the separator and the electrode can be improved.

[0060] In the present invention, the adhesive strength (peel strength) between the porous substrate and the porous coating layer of the separator may be 200 gf / 15 mm or more. Alternatively, the adhesive strength (peel strength) between the porous substrate and the porous coating layer may be 210 gf / 15 mm or more, or 220 gf / 15 mm or more. When the above numerical range is satisfied, there is an advantage that the adhesive strength between the porous coating layer located on the surface of the separator and the electrode can be maximized while preventing detachment between the porous substrate and the porous coating layer during the assembling process with the electrode.

[0061] The peel strength referred to in the present invention means the force required to peel the porous coating layer from the porous substrate by cutting a separation membrane to a size of 15 mm x 100 mm, attaching a double-sided adhesive tape to a glass plate, adhering the surface of the porous coating layer of the separation membrane to the adhesive tape, mounting an end of the adhered separation membrane in a UTM device, and applying a force of 180° at a measurement speed of 300 mm / min.

[0062] Meanwhile, in the present invention, the separator may further include other additives as necessary in addition to the binder polymer and inorganic filler as components of the porous coating layer.

[0063] The separator according to an embodiment of the present invention may be manufactured by preparing a composition for forming a porous coating layer, the composition including an inorganic filler and a binder polymer, applying the composition to at least one surface of a porous substrate, and drying the composition.

[0064] For example, first, a polymer solution is prepared by dissolving a binder polymer in a solvent, and then an inorganic filler is added to and mixed with the polymer solution to prepare a slurry for forming a porous coating layer. Next, the slurry is applied onto a porous substrate and left to stand for a predetermined time under a relative humidity of about 40% to 80% to solidify (dry) the binder polymer. At this time, phase separation of the binder polymer is induced. In the process of phase separation, the solvent moves to the surface of the porous coating layer, and the binder polymer moves to the surface of the porous coating layer along with the movement of the solvent, so that the content of the binder polymer in the surface of the porous coating layer becomes high. Pores are formed in the lower part of the surface of the porous coating layer due to the interstitial volume between the inorganic fillers, and the porous coating layer has a porous characteristic. In one embodiment of the present invention, the content of the binder polymer may increase toward the surface of the porous coating layer, but the inorganic filler and the binder polymer are mixed as a whole in the thickness direction of the porous coating layer, and a pore structure due to interstitial volumes between the inorganic filler particles is maintained from the bottom to the top of the porous coating layer, thereby allowing the resistance of the porous coating layer to be maintained at a low level.

[0065] Meanwhile, in one embodiment of the present invention, the concentration of solids excluding the solvent in the porous coating layer is preferably controlled to be in the range of about 10wt% to 80wt%. Non-limiting examples of the solvent used at this time include one compound or a mixture of two or more compounds selected from acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone, methyl ethyl ketone, cyclohexane, methanol, ethanol, isopropyl alcohol, propanol, and water.

[0066] The method of coating the porous substrate with the composition for forming a porous coating layer is not particularly limited, but it is preferable to use a slot coating method or a dip coating method. Slot coating is a method in which a composition supplied through a slot die is applied to the entire surface of a substrate, and the thickness of the coating layer can be adjusted by the flow rate supplied from a metering pump. Dip coating is a method in which a substrate is immersed in a tank containing a composition to coat it, and the thickness of the coating layer can be adjusted by the concentration of the composition and the speed at which the substrate is removed from the composition tank, and after immersion, it can be post-weighed using a Mayer bar or the like for more accurate control of the coating thickness.

[0067] The thickness of the separation membrane according to the present invention is not particularly limited, but may be in the range of about 5 to 50 μm or less, preferably about 5 to 20 μm, or about 5 to 15 μm.

[0068] The electrode assembly according to the present invention may include two electrodes having opposite polarities and a separator interposed between the two electrodes, and the separator may be the separator according to the present invention described above.

[0069] In the electrode assembly of the present invention, the adhesive strength (lamination strength) between the electrode and the separator may be 100 gf / 25 mm or more. Alternatively, the adhesive strength (lamination strength) between the electrode and the separator may be 110 gf / 25 mm or more, or 120 gf / 15 mm or more. When the laminate strength is within the above numerical range, it is possible to prevent deformation of the porous substrate due to relaxation of temperature and pressure conditions during the assembling process with the electrode, and also to reduce the folding phenomenon between the separator and the bonded electrode when the electrolyte is injected.

[0070] The laminate strength in the present invention refers to the adhesive strength between the electrode and the outermost surface (porous coating layer) of the separator facing one of the electrodes. In addition, the laminate strength in the present invention refers to the force required to peel off the electrode and the outermost surface (porous coating layer) of the separator facing the electrode by applying a force of 180° at a measurement speed of 300 mm / min, after preparing a negative electrode having a size of 25 mm×70 mm and a separator having a size of 25 mm×70 mm, stacking the prepared separator and electrode on top of each other and sandwiching them between 100 μm PET films, and then bonding them by heating at 60° C. and a pressure of 6.5 MPa for 1 second using a flat press, and then mounting the ends of the bonded separator and electrode in a UTM device.

[0071] The two electrodes having opposite polarity to be applied with the separator of the present invention may be positive and / or negative electrodes. The electrodes may be prepared by a method well known in the art in which an electrode active material is bound to an electrode current collector.

[0072] Among the electrode active materials, non-limiting examples of the positive electrode active material include conventional positive electrode active materials that can be used for the positive electrode of conventional lithium secondary batteries, and in particular, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or a lithium composite oxide that is a combination of these, etc., can be used.

[0073] Non-limiting examples of the negative electrode active material include conventional negative electrode active materials that can be used in the negative electrodes of conventional lithium secondary batteries, and in particular, lithium adsorbent materials such as lithium metal or lithium alloys, carbon, petroleum coke, activated carbon, graphite, or other carbons are preferable.

[0074] Non-limiting examples of positive current collectors include foils made of aluminum, nickel, or combinations thereof, and non-limiting examples of negative current collectors include foils made of copper, gold, nickel, or copper alloys, or combinations thereof.

[0075] In addition, the electrochemical device according to the present invention may include one or more electrode assemblies according to the present invention, specifically, an electrode assembly filled with an electrolyte.

[0076] The electrolyte that can be used in the electrochemical element of the present invention is A + B - For example, the salt may have the structure: + Li + , Na + , K + or a combination thereof, - PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3-, or a combination thereof, dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (γ-butyrolactone), or a mixture thereof.

[0077] The electrolyte injection may be performed at an appropriate step in the battery manufacturing process depending on the manufacturing process and required properties of the final product, i.e., before battery assembly or at the final step of battery assembly.

[0078] The present invention also provides a battery module including a battery having an electrode assembly as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to, a power tool that operates by receiving power supply, automobiles including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like, electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters (E-scooters), electric golf carts, and power storage systems.

[0079] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention can be modified into various other forms, and the scope of the present invention should not be construed as being limited to the examples detailed below. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0080] Working Example The separation membranes of the examples and comparative examples were produced by the following method.

[0081] Example 1 Manufacturing of a separation membrane including a porous coating layer A slurry for forming a porous coating layer was prepared by adding polyvinylidene fluoride-hexafluoropropylene (VDF:HFP=80:20, Solvay, Solef 21510), polyvinylidene fluoride-trichloroethylene (VDF:CTFE=80:20, Daikin, VT-475) and cyanoethyl polyvinyl alcohol as binder polymers to acetone, and adding AlOOH powder with an average diameter of 250 nm as an inorganic filler.

[0082] The concentration of solids (binder polymer and inorganic filler) excluding the solvent in each slurry was 18 wt%, and the weight ratio of the total binder polymer to the inorganic filler was 39:61. The slurry was mixed for about 2 hours using a painter shaker. The slurry was applied to both sides of a polyethylene polymer film (thickness about 9 μm, porosity about 40 to 45%) by deep coating method, and dried under a relative humidity of 45% to obtain a separation membrane. The drying was performed at room temperature. The drying time was maintained for about 10 minutes. The thickness of the porous coating layer of each obtained separation membrane was about 3 μm on both sides. The SEM image of the separation membrane manufactured in Example 1 is shown in FIG. 1. FIG. 1 shows an enlarged cross section of the surface of the porous coating layer / a cross section of the separation membrane of Example 1 / an enlarged cross section of the porous substrate (polyethylene polymer film) in that order.

[0083] Examples 2 to 3 and Comparative Examples 1 to 8 Separation membranes of Examples 2 to 3 and Comparative Examples 1 to 8 were produced by the same method as in Example 1, but the compositions were changed as shown in Table 1 below. In this case, the BET surface area of ​​the inorganic filler Al2O3 contained in Comparative Example 2 was 6.4 m 2 / g, and the BET surface area of ​​AlOOH is 16.1 m 2 / g, the BET surface area of ​​Comparative Example 2 was calculated to be (6.4 + 16.1) / 2.

[0084] [Table 1]

[0085] Evaluation of separation membrane properties The physical properties of the separators prepared in the examples and comparative examples are shown in Table 2 below.

[0086] [Table 2]

[0087] As can be seen from Table 2, when comparing Examples 1 to 3 with Comparative Examples 1 to 8, it was confirmed that Examples 1 to 3 were superior in adhesive strength to Comparative Examples 1 to 8. It was also confirmed that Examples 1 and 2 were superior in heat resistance stability to Comparative Examples 1 to 4.

[0088] In particular, Comparative Example 3 contained the same amount of binder polymer and inorganic filler as Examples 1 and 2, except for the BET surface area of ​​the inorganic filler. However, since the BET surface area of ​​the inorganic filler contained in Comparative Example 3 was smaller than that of Examples 1 and 2, the inorganic surface area covered by the binder polymer was reduced, and thus the adhesive strength (peel strength and lamination strength) could be improved, but since the packing between the inorganic fillers was inferior to that of Examples 1 and 2, the heat resistance properties were reduced, and the heat resistance stability was inferior.

[0089] Specifically, the evaluation of each physical property was carried out as follows.

[0090] (1) Evaluation of the adhesive strength (peel strength, gf / 15mm) between the porous substrate of the separation membrane and the porous coating layer

[0091] The separation membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 8 were cut into pieces measuring 15 mm×100 mm.

[0092] A double-sided adhesive tape was attached to a glass plate, and the surface of the porous coating layer of the prepared separator was attached to the adhesive tape. The end of the attached separator was then attached to a UTM device (Instron Corporation), and a force of 180° was applied at a measurement speed of 300 mm / min to measure the force required to peel the porous coating layer from the porous substrate.

[0093] (2) Evaluation of electrode-separator adhesion (lamination strength, gf / 25mm) The active material [natural graphite and artificial graphite (weight ratio 5:5)], conductive material [super P], and binder [polyvinylidene fluoride (PVdF)] were mixed in a weight ratio of 92:2:6, the resulting mixture was dispersed in water, and then coated onto copper foil to produce the negative electrode, which was then cut into a size of 25 mm x 70 mm.

[0094] The separation membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 8 were cut into pieces measuring 25 mm×70 mm.

[0095] The prepared separator and anode were stacked on top of each other, sandwiched between 100 μm-thick PET films, and bonded using a flat press, which was heated at 60°C and 6.5 MPa for 1 second.

[0096] The end of the bonded separator and the negative electrode were attached to a UTM device (Instron), and a force of 180° was applied at a measurement speed of 300 mm / min to measure the force required to separate the negative electrode from the separator bonded to the negative electrode.

[0097] (3) Evaluation of heat shrinkage properties at 150℃ The separators prepared in Examples 1-2 and Comparative Examples 1-4 were each cut to a size of 50 mm x 50 mm. The prepared separators were left in a convection oven set at 150°C for 30 minutes. After 30 minutes, the reduction in length of the separator compared to the initial length (50 mm x 50 mm) was calculated in % and the degree of thermal shrinkage was recorded.

[0098] (4) Evaluation of the loss length of the hot tip of the separation membrane The separation membranes manufactured in Examples 1-2 and Comparative Examples 1-4 were each cut to a size of 50 mm x 50 mm. The prepared separation membranes were subjected to a hot tip test using a UTM device. The diameter of the tip used in the hot tip test was 1 pi, and the tip temperature was 450°C, the measurement speed was 1 mm / s, and the measurement was stopped for 5 seconds. The disappearance length was obtained by measuring the diameter of the broken separation membrane hole with a ruler after the hot tip test.

Claims

1. A separator for an electrochemical element, comprising: The separation membrane comprises a porous substrate and a porous coating layer formed on at least one surface of the porous substrate, The porous coating layer includes a binder polymer and an inorganic filler, The inorganic filler includes an inorganic filler having a BET surface area value of 10 to 20 m 2 / g; A separator for electrochemical elements, which satisfies the following formula 1: [Formula 1] 23≦[content of inorganic filler (wt%)×BET surface area of ​​inorganic filler (m 2 / g)] / [content of binder polymer (wt %)≦28 (The content of the binder polymer and the content of the inorganic filler are based on 100% by weight of the total amount of the porous coating layer.)

2. The content of the inorganic filler is 50 to 80% by weight based on 100% by weight of the total amount of the porous coating layer; 2. The separator for an electrochemical device according to claim 1, wherein the content of the binder polymer is 20 to 50 wt % based on 100 wt % of the total weight of the porous coating layer.

3. 2. The separator for electrochemical elements according to claim 1, wherein the binder polymer is polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polybutyl acrylate, polybutyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyethylene vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxyl methyl cellulose, or a mixture of two or more of these.

4. 2. The separator for an electrochemical device according to claim 1, wherein the adhesive strength (peel strength) between the porous substrate and the porous coating layer of the separator is 200 gf / 15 mm or more.

5. An electrode assembly comprising two electrodes having opposite polarities and a separator interposed between the two electrodes, the separator comprising the separator according to any one of claims 1 to 4.

6. The electrode assembly according to claim 5 , wherein an adhesive strength (lamination strength) between the electrode and the separator is 100 gf / 25 mm or more.

7. An electrochemical device comprising one or more electrode assemblies according to claim 5.

8. The electrochemical device according to claim 7 , wherein the electrochemical device is a lithium secondary battery.

Citation Information

Patent Citations

  • Electrode assembly and secondary battery equipped with electrode assembly

    JP2009170421A

  • Separator for nonaqueous electrolyte battery and nonaqueous electrolyte battery

    JP2015099801A

  • Separator for electrochemical device and electrochemical device containing same

    US20210028428A1

  • Lithium ion secondary battery

    WO2012131883A1

  • Non-aqueous electrolyte type secondary battery

    WO2013073011A1